Well-differentiated papillary mesothelial tumor of pleura: A case report - Anuradha Bardia; Ayesha Afreen Islam; Keya Basu; Uttara Chatterjee (Annals of Medical Science and Research)
Mesotheliomas are rare neoplasms that primarily affect the mesothelial cells lining the lungs, abdomen, heart, or testicles. It is primarily caused by exposure to asbestos fibers, with a latency period of several decades before manifestation of symptoms. Due to overlapping cytomorphological features with lung carcinoma, a definitive cytological diagnosis still remains a challenge for pathologists. This case report presents a case of papillary mesothelioma; its clinical and radiological presentations, with special emphasis on cytological diagnosis; and the role of histopathology and Immunohistochemistry as a confirmatory tool. A 43-year-old factory worker reported to the Chest Outpatient Department (OPD), with chest pain and difficulty in breathing for the past 2 months. Radiological findings suggested a right-sided pleural mass with pleural effusion. FOB findings were unremarkable. Subsequently, CT-guided FNAC was done and slides submitted to cytopathology evaluation. The cytomorphological features indicated papillary mesothelioma, which was further confirmed by histopathology and immunohistochemistry. Though histopathology remains a gold standard for diagnosis of papillary mesothelioma, proper clinical and radiological correlation and thorough examination of the cytomorphological features on cytology smears can help in early diagnosis and better prognosis of the patients.